(untitled) (Journal of Geography, Meteorology and Environment, 2025)
Hydrological modeling of ungauged basins is necessary for decision and policymaking in water resources management. The Mamu River Basin is characterized by a wide range of environmental pressures such as erosion-caused devastation. The impact of climate change is likely to have considerable implications for water resource planning in the Basin. Despite these challenges, there is no gauged data available to evaluate the water resources of the Mamu River Basin. The objective of this study is to simulate river discharge in the ungauged Mamu River Basin using Soil and Water Assessment Tools (SWAT). A regionalization approach was employed to simulate the river flow at the Ebenebe axis of the Mamu River. Calibrated and validated model parameters from gauged Imo River were transferred to the Mamu River Basin. Shuttle Radar Topographic Misson-Digital Elevation Model (SRTM-DEM), land use, soil data, and rainfall data for the Mamu River Basin were used to improve the model. The SWAT model simulated streamflow for the basin and this was validated using discharge measurements along the Mamu River from 01/01/2021to 31/12/2022. During the validation process, the model performance indicators, NSE, R2, and PBIAS values were 0.77, 0.95, and 15 respectively. This study showed that the SWAT model can simulate river discharge in an ungauged river basin and will enhance our understanding of the hydrological response of the ungauged Mamu River Basin to environmental changes.